Effect of sample length on the time needed to reach the steady state case - Muhyi, Muhsin Ubayd (Journal of University of Babylon for Engineering Sciences, 2019)
In this study, ANSYS-14 was used to study the effect of the length of the sample on the time needed to reach steady state (S.S.t) for the transient heat transfer. Three samples were studied in different lengths (15, 30 and 45 cm), 2 cm high, in addition to the selection of three materials with different thermal properties and applied to different lengths. One side of the three samples was exposed to a temperature at 100 ° C, while the other side was exposed to thermal load at 25 ° C and the sample was isolated from the top and bottom surfaces. The objective of this study is to determine the effect of the time reach to the steady state when changing the length of the sample exposed to constant thermal load and materials, depending on the distance from the hot face of all lengths at a number of points (3, 6, 9 and 12) cm. From the results of the time obtained numerically from the ANSYS-14 program, the time to reach the steady state was determined when the difference between the sample temperature reached with the previous grade of 0.001.The results indicated that the time required to reach the steady state (S.S.t) increases by increasing the length of the sample in the selected points when constant thermal diffusivity (α) ,where the time needed to reach the steady state of the copper material ranged between (879-1085) seconds at a length of 15 cm and (2112- 3005) seconds at length 30 cm and (2871-4937) seconds at a length of 45 cm as well as the results showed that the time required to reach the steady state increased with the thermal diffusivity decrease where the time required to reach the steady state of the copper of the highest thermal diffusivity ranged between (879-4937) seconds for all lengths while the time required to reach the steady state of the material of the lowest thermal diffusivity (hardboard) is between (168400-1078000) seconds.